Analysis of Computer Textbook for the Second Intermediate Grade According to Digital Citizenship - Hazim Ibrahim, Zainab (Opción, 2019)
The research aims to build a list of digital citizenship axes and standards and indicators emanating from them, which should be included in the content of the computer textbook scheduled for second grade intermediate students in Iraq, and the analysis of the above mentioned book according to the same list using the descriptive analytical method ((method of content analysis)). The research community and its sample consisted of the content of the comput- er textbook scheduled for the second year intermediate students for the aca- demic year 2018-2019, and the research tool was built in its initial form after reference to a set of specialized literature and previous studies that dealt with topics related to digital citizenship, and the authenticity of the tool was con- firmed. The researcher adopted the idea unit (explicit and implicit) as a unit of analysis, and it was confirmed the validity and stability of the analysis. The research found that the content of the computer textbook scheduled for the second intermediate students dealt with the criteria of digital citizenship in unequal proportions, and did not take into account the balance and regula- tion, as the proportion of standards (digital behavior, digital communication, digital literacy, digital health and safety, digital security) respectively( 12.11%, 40.36%, 45.29%, 0.45%, 1.79%) in the textbook content, and the content of the book omitted standards (digital access, digital laws, digital trade, digital rights and responsibilities).